The Long-run Performance of Initial Public Offerings- Evidence from the A-share Shanghai Stock Exchange - Yu, Lijun (2006)
The long-run underperformance of initial public offerings (IPOs) is one of the hotspots in the IPO fields. It is essential to study the long-run performance of IPOs in China, because it benefits how to improve the efficiency of IPO market and provides insight of emerging market. It can also add to the international evidences on IPOs performance. This dissertation provides evidence to support the underperformance of IPOs in A-share Shanghai Stock Exchange, in China. The evidence is based on the data from the stock markets in Shanghai over the period from 1st January 2000 to 31st December 2002. Time-series analysis is used to test the long-run market-adjusted returns of IPOs in China. It also attempts to fill the great gap in existing studies on the explanations for the long-run stock price anomy. Regression analysis is adopted to provide reasons for explaining the long-run performance of IPOs.